ON THE SYSTEMATICS OF SMALL SPIRIFERIDS FROM THE UPPER DEVONIAN OF THE SOUTHERN TIMAN MOUNTAINS - Oleneva N.V. (My University, 2004)
The type species of the genus Conispirifer Ljaschenko, C. rotundus Ljaschenko, is revised based on the material from the Upper Devonian of the southern Timan. C. rotundus was established based on juveniles of Tenticospirifer komi Ljaschenko. Two new genera of Upper Devonian spiriferids, Microspirifer (with the type species M. nikonovi) and Cyrtinaria (with the type species C. nana) are described.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская